PEMBUATAN PAVING BLOCK BERONGGA MENGGUNAKAN AGREGAT BERGRADASI SERAGAM - Mulyati, Mulyati; Misbah, Misbah; Aryf Prasetyo, Dymas (ITP Press, 2025)
Pervious paving blocks are type of concrete brick (paving block) that is designed with pervious or gaps in the interior which become water absorption pathway into the soil, thereby helping reduce waterlongging and supporting a natural drainage system. This research aims to obtain compressive strength values and maximize the infiltration rates of perforated paving bocks using uniformly graded aggregates. The coarse aggregate used is split sizes 2-10 mm 1nd 10-20 mm with a mixture ratio of 1 Pc : 2 Split, 1 Pc : 3 Split, and 1 Pc : 4 Split. The paving block test object uses a rectangular mold with dimensions of 20 cm x 10 cm x 6 cm. Tests carried out on paving block test specimens were compressive strength and infiltration rate at the age of the test object of 28 days. Test results for compressive strength and infiltration rate of paving block specimens using a 5-10 mm split for a ratio of 1:2, 1:3, and 1:4 respectively, the compressive strength was 14.50 MPa; 8.17 MPa; 5.33 MPa, and an infiltration rate of 3.16 mm/s; 6.15 mm/s; 8,61 mm/sec, and using a split 0f 10-20 mm for a ratio of 1:2, 1:3, and 1:4 respectively, the compressive strength is 21.83 MPa; 10.87 MPa, 7.30 MPa, and an infiltration rate of 4.04 mm/s; 7.18 mm/s; 10.04 mm/sec. Using a larger uniformly graded aggregate size can increase the compressive strength and maximize the infiltration rate of paving block. The mixture ratio using more uniformly graded aggregate can increase the infiltration rate but decrease the compressive strength of the paving block. Keywords: Compressive Strength, Infiltration Rate, Hollow Paving Blocks, Uniformly Graded Aggregate, Mix Ratio, Continuous Drainage